2021
DOI: 10.1101/2021.02.24.21252047
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of a surrogate virus neutralization test for high-throughput serosurveillance of SARS-CoV-2

Abstract: High-throughput serological tests that can detect neutralizing antibodies against SARS-CoV-2 are desirable for serosurveillance and vaccine efficacy evaluation. Although the conventional neutralization test (cVNT) remains the gold standard to confirm the presence of neutralizing antibodies in sera, the test is too labour-intensive for massive screening programs and less reproducible as live virus and cell culture is involved. Here, we performed an independent evaluation of a commercially available surrogate vi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Furthermore, the assay allows for high sample-throughput, as samples are analyzed in one defined dilution and no serial dilution is required. Validation studies showed high specificity and sensitivity of the assay [ [30] , [31] , [32] , [33] , [34] ] however, a recent study demonstrated low sensitivity in sera with low neutralizing titers and only moderate linearity with the PRNT 50 [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the assay allows for high sample-throughput, as samples are analyzed in one defined dilution and no serial dilution is required. Validation studies showed high specificity and sensitivity of the assay [ [30] , [31] , [32] , [33] , [34] ] however, a recent study demonstrated low sensitivity in sera with low neutralizing titers and only moderate linearity with the PRNT 50 [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neutralization test methods using replication-defective pseudotyped viral particles have been developed; however, these still require live-cell culture, considerable manual handling steps and, consequently, inevitable variance in neutralization results. Although surrogate neutralization assays have been developed and validated,(10, 36) their applied competitive assay principle goes along with a rather small dynamic range, which limits resolution of change in high titer vaccination samples. In addition, challenges of semi-automatable methods and costs remain.…”
Section: Discussionmentioning
confidence: 99%